2008
DOI: 10.1007/s00468-008-0236-5
|View full text |Cite
|
Sign up to set email alerts
|

Climate-related variability in carbon and oxygen stable isotopes among populations of Aleppo pine grown in common-garden tests

Abstract: The Aleppo pine (Pinus halepensis Mill.) is found in the Mediterranean under a broad range of moisture and thermal conditions. Differences in severity and duration of water stress among native habitats may act as selective forces shaping the populations' genetic make-up in terms of contrasting drought strategies. We hypothesised that these strategies should translate into intraspecific variation in carbon isotope composition (d 13 C, surrogate of intrinsic water-use efficiency, WUE i ) of wood holocellulose, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(136 citation statements)
references
References 41 publications
12
123
0
1
Order By: Relevance
“…IIB), which suggests that the WUE was affected by both, external and internal factors, like water availability and gas exchange performance, or by their interaction. Higher δ 13 C variability in the drier trial site was also observed by Voltas et al (2008) in Pinus halepensis populations.…”
Section: Carbon Isotope Compositionmentioning
confidence: 52%
“…IIB), which suggests that the WUE was affected by both, external and internal factors, like water availability and gas exchange performance, or by their interaction. Higher δ 13 C variability in the drier trial site was also observed by Voltas et al (2008) in Pinus halepensis populations.…”
Section: Carbon Isotope Compositionmentioning
confidence: 52%
“…As reviewed by Warren et al (2001) C from P. halepensis wood as a proxy for WUE estimation has been previously confirmed by (Ferrio et al 2003;Voltas et al 2008Voltas et al , 2015.…”
Section: Carbon Isotopesmentioning
confidence: 67%
“…is a long-lived conifer, widely distributed across the Mediterranean Basin, where it can be found across environments encompassing a broad range of moisture and thermal conditions. It has also remarkable capacity to cope with dry and low-fertility environments (Voltas et al 2008;Santos-del-Blanco et al 2013). Previous studies suggest that Aleppo pine populations expanded westwards all around the Mediterranean basin from some refugia located in the southern part of the Balkan Peninsula (Grivet et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Also, studies that integrate a comprehensive set of fitness-related traits will provide a more realistic picture of adaptive strategies (Pigliucci, 2004). An integrated analysis of further traits such as constitutive and induced defences (Sampedro et al, 2011), drought resistance (Voltas et al, 2008), cold tolerance (Climent et al, 2009), phenology (Salmela et al, 2013, serotiny (Hernández-Serrano et al in prep), stem architecture (Sierra-de-Grado et al, 1999), ontogenetic heteroblasty , bark thickness and seed size and dispersal ability (Santos-del-Blanco & Climent, 2011) will be highly valuable.…”
Section: Costs Of Reproduction and Trade-offsmentioning
confidence: 99%
“…Los caracteres más comúnmente estudiados en pinos mediterráneos en ensayos de ambiente común han sido por un lado el crecimiento (ALÍA et al 1995, CHAMBEL et al 2007) y por otro, caracteres fisiológicos de valor adaptativo, como la resistencia al frío (CLIMENT et al 2009), a la sequía , VOLTAS et al 2008) o fenología (CODESIDO y FERNANDEZ-LOPEZ 2009). Desde un punto de vista evolutivo, un carácter se considera adaptativo si tiene una influencia positiva en el número de descendientes producidos por un organismo.…”
Section: /13unclassified